Splenic infarct due to scrub typhus - Selvin Sundar Raj; Adhiti Krishnamoorthy; Manjeera Jagannati; Kundavaram PP Abhilash (Journal of Global Infectious Diseases, 2014)
Scrub typhus is a mite borne infectious disease that has the potential to involve multiple organs and can be fatal. Involvement of the abdomen in the form of hepatitis, gastric ulcerations and pancreatitis are well-documented, the pathology being disseminated vasculitis. However involvement of the spleen in scrub typhus is extremely rare and is reported only in a few autopsy studies. We report the case of a 50-year-old lady who presented with fever and left upper quadrant abdominal pain due to a splenic infarct due to scrub typhus.